Urinary profile of catecholamines and metabolites in Parkinson patients with deep brain stimulation. (17th May 2013) - Guimarães, J.; Vieira‐Coelho, M. A.; Moura, E.; Afonso, J.; Rosas, M. J.; Vaz, R.; Garrett, C.
<x xml:space="preserve">Abstract</x> Background and purpose Deep brain stimulation of the subthalamic nucleus (DBS‐STN) is thought to continuously alter the activity of STN neurons in Parkinson's disease (PD). A chronic decrease in the levodopa dose with continuous STN stimulation may induce plastic neuronal changes. Objective The objective of this work was to study urinary excretion of catecholamines in patients with PD before and after DBS‐STN. Methods Twenty‐three patients were submitted to DBS‐STN, and evaluated before and after surgery with respect to catecholamines and metabolites in 24‐h urine measured by high‐performance liquid chromatography with electrochemical detection. Results Of the 23 patients evaluated, a significant decrease of about 60% in the urinary excretion of l‐3, 4‐dihydroxyphenylalanine (l‐DOPA; in nmol/mg creatinine/24 h) was observed 1 week after DBS‐STN. Moreover, in 17 patients with a follow‐up of 8 weeks after surgery, there was a further 50% decrease in urinary l‐DOPA levels, dropping to about 75% of the values before surgery. There was also a significant decrease in dopamine (DA) and 3, 4‐dihydroxyphenylacetic acid (DOPAC) levels 1 week after DBS‐STN that was no longer present 8 weeks after. A significant increase in the DA/l‐DOPA ratio was observed 1 week after surgery, with a further increase 8 weeks after surgery. Conclusion After DBS‐STN, the DA/l‐DOPA ratio, an indirect measure of DA synthesis, increased. These results show that DBS‐STN may improve the efficacy of oral levodopa.